Anthropogenic transformation of hydrographic network of Minsk for the historical period - Zmachynski, Alexander S. (Journal of the Belarusian State University. Ecology, 2019)
The paper deals with anthropogenic transformation of hydrographic network of Minsk for the historical period that has been developed in two main directions. The natural waterways were reduced on extend or totally dissapeared during the development of the territories, artificial reservoirs of different function were created on the remained waterways.